Effect of hydrogen passivation on electrical and optical properties of ZnO@ZnS heterostructure NW by first-principles. (19th May 2018) - Huang, Baorui; Zhang, Fuchun; Yang, Yanning; Zhang, Zhiyong; Lv, Yuanyuan
ABSTRACT: The effects of hydrogen passivation on ZnO/ZnS and ZnS/ZnO core/shell NW were studied based on Density Functional Theory of the first-principles. The results indicate that the effect of hydrogen passivation on geometry structural relaxation of ZnS/ZnO core/shell NW is tremendous, and the band gap increased from 1.21 to 2.46 eV. For ZnO/ZnS core/shell NW, hydrogen passivation greatly enhances the plasma frequency, which has little effect on the geometrical structure, band gap width and optical properties. The ZnO/ZnS core/shell NW has high light transmittance in the visible light region, and have unique narrow absorption peak in the ultraviolet region. Therefore, it is an excellent material for the preparation of transparent UV light application.